2014
DOI: 10.1093/jxb/eru249
|View full text |Cite|
|
Sign up to set email alerts
|

The Aux/IAA gene rum1 involved in seminal and lateral root formation controls vascular patterning in maize (Zea mays L.) primary roots

Abstract: SummaryRNA-Seq of RUM1-dependent gene expression in maize primary roots, in combination with histological analyses, highlighted the regulation of auxin signal transduction by RUM1 and its role in vascular development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 51 publications
(80 reference statements)
1
48
0
1
Order By: Relevance
“…S3). Recently, we have also shown that the rootless with undetectable meristem1 mutant, which is defective in lateral root formation, displays significant inhibition of ubiquitindependent protein degradation and cell cycle/division processes (Zhang et al, 2014). Thus, our RNA-Seq results, together with the finding that SKP2B overexpression promotes KRP1 degradation in Arabidopsis (Ren et al, Figure 5.…”
Section: Local High Nitrate Promotes Auxin-mediated Cell Cycle Activasupporting
confidence: 77%
“…S3). Recently, we have also shown that the rootless with undetectable meristem1 mutant, which is defective in lateral root formation, displays significant inhibition of ubiquitindependent protein degradation and cell cycle/division processes (Zhang et al, 2014). Thus, our RNA-Seq results, together with the finding that SKP2B overexpression promotes KRP1 degradation in Arabidopsis (Ren et al, Figure 5.…”
Section: Local High Nitrate Promotes Auxin-mediated Cell Cycle Activasupporting
confidence: 77%
“…In line with the differentiation status of the stele, several GO terms involved in lignin biosynthesis (related to the bins cell wall and secondary metabolism) were overrepresented in this tissue (Supplemental Table S1). Lignin is deposited in the xylem elements of the stele to provide structural support (Vermerris et al, 2010;Zhang et al, 2014). In line with the overrepresentation of lignin biosynthesisrelated GO terms, six laccases (GRMZM2G146152_P01, GRMZM2G164467_P01, GRMZM5G814718_P01, GRMZM-2G367668_P01, GRMZM2G388587_P01, and GRMZM2-G305526_P01) were accumulated exclusively in the stele (Supplemental Data Sets S1 and S3).…”
Section: Discussionmentioning
confidence: 91%
“…DII responded to both exogenous IAA applied to leaf pieces and roots as well as endogenous auxin signaling in leaves, roots, and developing tassels. The important role of auxin in maize development (Forestan and Varotto, 2012;Galli et al, 2015;McSteen, 2010;von Behrens et al, 2011;Yu et al, 2016;Zhang et al, 2014) and during the cell cycle (Del Pozo and Manzano, 2014;Himanen et al, 2002) highlights the utility of the DII marker.…”
Section: Discussionmentioning
confidence: 99%
“…In maize (Zea mays), auxin contributes to inflorescence development (Galli et al, 2015), tassel branching (Gallavotti et al, 2008a), and root structure (Jansen et al, 2012;Zhang et al, 2014). The currently available auxin reporter in maize uses the synthetic promoter element DR5 to drive the expression of an endoplasmic reticulum retained Red Fluorescent Protein (DR5rev::mRFP-er, DR5) in response to increased auxin.…”
mentioning
confidence: 99%